The Role of Tax Volunteers in The Renjani Program at The Jember Primary Tax Office - Lisa Wati; Windi Istiqoh Maulidya; Bagos Muchlis; Abdul Wadud Nafis (Medikun Publisher, 2024)
This research aims to explore the role of tax volunteers in supporting the success of the Renjani program at the Jember Primary Tax Office. The Renjani program aims to increase tax compliance among the public through education and socialization approaches. The research method used was participatory observation of tax volunteers and related Jember Primary Tax Office officials. The results showed that tax volunteers have a significant role in supporting the Renjani program, both in approaching the public and in implementing socialization and education activities. They help convey information about tax obligations in a more easily understandable way for the public, increase awareness of the importance of tax compliance, and provide technical assistance to taxpayers. Thus, the role of tax volunteers at the Jember Primary Tax Office can be considered as one of the key factors in the success of the Renjani program in achieving the goal of increasing tax compliance in the community. This study provides a more comprehensive insight into how collaboration between tax volunteers and tax institution officials can optimize the effectiveness of tax socialization and education programs.